2003
DOI: 10.1262/jrd.49.175
|View full text |Cite
|
Sign up to set email alerts
|

Pfaffia paniculata-Induced Changes in Plasma Estradiol-17.BETA., Progesterone and Testosterone Levels in Mice

Abstract: Abstract. The present study undertook chemical analysis of components of Pfaffia paniculata roots. In addition, an animal experiment was conducted in which mice had ad libitum access to water enriched with powdered P. paniculata root for 30 days. Changes in plasma concentrations of estradiol-17β and progesterone in female mice and of testosterone in male mice were ascertained. The results revealed that P. paniculata roots contain two types of phytosteroids, β-sitosterol and stigmasterol, in addition to other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The results showed that the extract consisted mainly of triterpenes and saponins, though the presence of phenolic compounds, flavonoids and alkaloids was also evidenced in agreement with the previous data [28][29][30][31][32]. Other classes of substances, including tannins, anthraquinones, coumarins and cyanogenic glycosides, were not detected.…”
Section: Phytochemical Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…The results showed that the extract consisted mainly of triterpenes and saponins, though the presence of phenolic compounds, flavonoids and alkaloids was also evidenced in agreement with the previous data [28][29][30][31][32]. Other classes of substances, including tannins, anthraquinones, coumarins and cyanogenic glycosides, were not detected.…”
Section: Phytochemical Analysissupporting
confidence: 89%
“…Different compounds, such as pfaffic acid, nortriterpenoid saponins derived from the pfaffic acid and denominated pfaffosides A, B, C, D, E, and F, which are chemically related to ginsenosides, have been isolated from P. paniculata, along with phytosterols, such as the β-sitosterol, stigmasterol and their glucosides [28][29][30][31][32]55]. The phytochemical analysis performed in our study showed that the P. paniculata extract contained a series of compounds belonging to these chemical classes.…”
Section: Discussionmentioning
confidence: 66%
“…Maca contains phytosterols, such as campesterol, stigmasterol and b-sitosterol [9] which play a role in the expression of sex hormones [45] and gonadal steroidogenic acute regulatory protein (StAR) [46]. Phytosterol intake and increased plasma levels, however, have also been associated with a low incidence of CHD.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Beta-Ecdysone, another plant steroid isolated from Pfaffia facilitates cellular oxygenation [32]. Nutritional analysis has found that Pfaffia contains 19 different amino acids, a large number of electrolytes and trace minerals including iron, magnesium, cobalt, silica, zinc and the vitamins A, B-1, B-2, E, K, and pantothenic acid [33][34][35][36][37][38][39][40]. It is especially high in the trace element germanium which is considered an oxygenator and is used as a nutritional supplement for the immune system.…”
Section: Chemical Compoundsmentioning
confidence: 99%